1974
DOI: 10.1002/cne.901560402
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the synaptic endings on the Mauthner cell of the goldfish

Abstract: This study has investigated the fine structure of the Mauthner cell of the goldfish. The animals were divided into three groups of three fish and each group was perfused with one of the following fixatives: osmium tetroxide, glutaraldehyde, or formaldehyde. Large myelinated club endings and smallvesicle boutons (SVBs) are found on the distal part of the lateral dendrite. The club endings have the structure of the mixed synapse and contain large, round synaptic vesicles. The SVBs, appearing as small boutons, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
2

Year Published

1974
1974
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(89 citation statements)
references
References 42 publications
8
79
2
Order By: Relevance
“…S4, and Movie S1) and very prominently in its ''axon cap'' (Fig. S4A) (19). Confirming the specificity of the monoclonal ZO-1 antibody in recognizing its goldfish ortholog, we observed positive labeling of contacts at known sites of tight junctions between cells of the ependema and liver (data not shown).…”
supporting
confidence: 58%
“…S4, and Movie S1) and very prominently in its ''axon cap'' (Fig. S4A) (19). Confirming the specificity of the monoclonal ZO-1 antibody in recognizing its goldfish ortholog, we observed positive labeling of contacts at known sites of tight junctions between cells of the ependema and liver (data not shown).…”
supporting
confidence: 58%
“…4C,). All stained terminals had a mean diameter of 1.97 f: 0.43 pm (n = 22), in agreement with previous electron microscopic data for the size of SVBs (Nakajima, 1974). Electron microscopic studies with GABA and somatostatin antisera on serial ultrathin sections confirmed the existence of these three populations of SVBs (Fig.…”
Section: Ultrastructure Of Somatostatin-immunoreactive Boutonssupporting
confidence: 90%
“…The density of gold particles was the highest in LMCEs. These endings transmit both electrically and chemically (Furshpan, 1964;Korn and Faber, 1976;Lin and Faber, 1988) in agreement with electron microscopic (Roberston et al, 1963;Nakajima, 1974) and freezefracture (Tuttle et al, 1986) data. Previous iontophoretic (Diamond and Roper, 1973) and pharmacological (Wolszon and Faber, 1988) studies suggest that the chemical component of LMCEs is mediated by glutamate.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Auditory afferents terminating as mixed (electrical and chemical) synapses known as large myelinated club endings on the goldfish Mauthner (M-) cells ("club endings") (Bartelmez, 1915;Furshpan, 1964;Nakajima, 1974;Lin and Faber, 1988) provide a convenient in vivo model in the vertebrate CNS, amenable to experimental manipulation, to study how efficient bi-directional communication is achieved despite unfavorable electrical and geometrical conditions. This relatively homogeneous group of synaptic contacts is tightly segregated to the distal portion of the lateral dendrite of the M-cells (Bartelmez, 1915), a pair of large reticulospinal neurons responsible for the organization of escape responses evoked by sound and other senses (Eaton et al, 2001).…”
Section: Introductionmentioning
confidence: 99%